Розробка графічного інтерфейсу для взаємодії з бібліотекою manim з можливістю розширення функціоналу - Сало, С. С. (ХНУРЕ, 2025)
Mathematical visualization plays a crucial role in education and research, aiding comprehension of complex concepts. Manim is a powerful library for creating mathematical animations, yet its reliance on Python programming limits accessibility for many educators and researchers. This work is devoted to the development of a graphical interface for Manim, designed to enable users to create mathematical animations without programming knowledge. Developed using PyQt5, the interface allows intuitive object and animation management, with functionality extensible via a file-based system rather than hardcoded definitions.
Keywords: розробка графічного інтерфейсу; Manim